Hello Everybody,

I'm really struggling with this following 3-part problem. Any help or guidance through them would be greatly appreciated.

1a.Using u-substitution, solve (x^2 - 2)^2 - 3(x^2 - 2) - 4 = 0.

So I was able to figure this problem out using u-substitution and gotx = (±) square root of 6 & x = ±1.

1b.The quadratic formula solves equations of the formax^2 +bx+c= 0. Find the formula that solvesa(x^2 -d)^2 +b(x^2 -d) +c= 0

For this problem, their looking for a formula but I'm not sure which one or how to find it.

1c.Use your formula from part (b) to verify your answers from part (a).

For this last part, part 1b must be completed.

## Bookmarks